Prevalence of human papillomavirus types in women with pre-neoplastic and neoplastic cervical lesions in the Federal District of Brazil - Camara, Geni NL (2003)
As a contribution to the public health authorities in planning prophylactic and therapeutic vaccine strategies, we describe the prevalence of human papillomavirus (HPV) types in women presenting abnormal cytological results in Pap smear screening tests in the Federal District, Central Brazil. We studied 129 cervical scraping samples from women whose cytological tests showed either pre-neoplastic or neoplastic lesions. Amplification of HPV DNA was performed by polymerase chain reaction using consensus primers MY09 and MY11 followed by identification of isolates by restriction fragment length polymorphism. We detected HPV DNA in 62% of the samples, including HPV-16 in 43.8%, HPV-58 in 12.5%, HPV-31 in 10%, HPV-53 in 6.3%, each of HPV-18 and HPV-33 in 3.8% of the isolates. Other types (HPV-35, -52, -66, -CP8304, -6, -11, and -CP8061) were less frequent (= or < 2.5% each). The prevalence of HPV-58 was relatively higher in this population than in data in South America, but similar to results obtained in other studies in Latin America, Europe, and Eastern Asia. Case-control studies need to be carried out to establish the association between the prevalence of HPV types specially the less frequent high-risk types and cervical cancer.